Paulownia trees as a sustainable solution for CO2 mitigation: assessing progress toward 2050 climate goals - Ghazzawy, Hesham S.; Bakr, Ahmed; Mansour, Abdallah Tageldein; Ashour, Mohamed (Frontiers in Environmental Science, 2024)
Due to the progressive climate changes on our planet, scientists are interested in solving this issue since it threatens not only certain regions or countries but also the world's ecosystems and economy. Therefore, minimizing carbon dioxide (CO2) emissions and reducing atmospheric levels are global priorities. Thus, it is necessary at this moment to develop an appropriate approach to reduce or stabilize CO2 levels in the atmosphere. However, CO2 capture projects are long-term, low-profitable, and high-risk environmental projects. Consequently, it is necessary to find an appropriate and sustainable CO2 capture approach that is efficient in reducing atmospheric CO2 levels while having a safe impact on the environment. While carbon (C) is the key basic component used to produce biological compounds by photosynthetic organisms in terrestrial plants, the C pathway is a key factor affecting the capture CO2 by photosynthetic organisms. Among photosynthetic organisms, Paulowina, a multipurpose tree, is popular around the world for its timber and its potential role in CO2 sequestration. Paulownia spp. belongs to the Paulowniaceae family and comprises a group of trees. These trees are primarily found in southeastern Asia, particularly in China, and have been intentionally grown for more than two millennia due to their ornamental, cultural, and medicinal value. The number of Paulownia species varies depending on taxonomic classification, ranging from 6 to 17. Among them, P. tomentosa, P. elongata, P. fortunei, and P. catalpifolia are the most widely recognized and favored species. The present review provides a comprehensive technical-economic scenario for the capture of one million tons of CO2 by Paulownia trees (as terrestrial plants model, grown in 2400 ha -1 ). P. tomentosa can be utilized in agroforestry systems to mitigate greenhouse gas (GHG) emissions within urban cities and emphasize the carbon storage potential of agroforestry. In conclusion, Paulownia trees as an environmental mass project showed great encouragement to investors and governments to expand these types of projects to achieve global climate goals by 2050.